Proposed Business Strategy for PT. Pilar Kencana Tama to Win the Increasing Competition - Singgih Wicaksono, Ariobimo (Journal of Economics and Business UBS, 2023)
PT. Pilar Kencana Tama has several limited capabilities that weaken the company's competitiveness and external factors that often hinder its business operations in the construction services business industry. Meanwhile, market demand for business products from contracting companies is increasing along with the increasing population growth in Indonesia. A new business strategy is required that can support Pilar to develop in the long term and take advantage of the momentum of high market demand for civil construction so that Pilar can have a high market share in its business industry. The approach to solving strategic problems owned by Pilar is with an analysis framework of the internal and external business environment to design a new business strategy. The external environmental analysis is used by the PESTEL framework which includes Political, Economic, Social, Technological, Environmental and Legal aspects. The internal environment analysis is used by the stakeholder mapping framework, VRIO, the BCG (Boston Consulting Group) growth share matrix, and the business model canvas. Other analytical data were obtained through qualitative interviews with Pilar’s director, external parties regarding new business model proposals, quantitative surveys with prospective customers and several literature reviews to support the data analysis. Both types of analysis are summarized in the form of SWOT analysis to serve as basic parameters for strategy formulation using the Diamond Strategy and a new business model canvas as well as additional strategy formulation using Strategy Moves to determine how Pilar attacks on competitor companies if necessary. The results of the study show the company's advantages such as the big amount of its heavy equipment resources and the company's orientation that emphasizes quality over quantity. However, Pilar also has weaknesses from its operational capacity such as unproductive and uncreative human resources, lack of business line expansion, and only has one channel to market its business products, so that Pilar cannot easily jump right to try new business models outside of the business model which has already been done. With the analysis results related to other construction model business opportunities, Pilar needs to implement a new business model proposal by implementing several predetermined strategies. The proposed strategy to support Pilar's success in running the new business model is by overhauling the company's internal resources, implementing the Diamond Strategy that has been determined, and implementing several aspects that have been calculated related to the determination of the level of importance of criteria from customers in buying products related to the proposed new business model. Pilar also needs to use the Differentiated Circle concept in target market segments to attack larger competitor companies that have long been in the area where Pilar will carry out the proposed new business model.